Caracterização morfo-agronômica e química dos frutos de ecótipos de açaí (Euterpe oleracea Mart.) de diferentes ambientes da baixada maranhense - Santos, Flaviana Almeida dos (2019)
Brazil has a variety of fruit species, especially native, but little researched, such as açai (Euterpe oleracea Mart.) regarding its development in lowland and grounded environments. The objective was to characterize morpho-biometric and chemical parameters of fruits of açaí ecotypes of the environments (lowland and grounded) in Baixada Maranhense. The analyzes were performed at UEMA and UFMA in São Luís- MA. For the morpho-agronomic attributes of the fruits of the açaí ecotypes in the two environments, there seems to be phenotypic variability in the E. oleracea population, for fruit mass per bunch, total mass of bunch, mass of rachis plus rachis, number of fruits per bunch, transverse diameter of fruits and length of rachis. The ecotypes “Caminho Novo” (lowland environment) and “Caeteto” (grounded environment) were more promising in terms of fruit production and proportion in relation to the total mass of the bunch. In 83% of the ecotypes, their fruits had an oblate shape. The chemical results related to total soluble solids (TSS), pH and pulp ratios of the fruits were significantly affected by the ecotypes, contrary to the acidity values. The pulps of the fruits of the "Santana dos Nunes” and “Olho d’água dos Gomes” ecotypes (lowland environment) and “Água Preta” and “Caeteto” (landfill environment) differed statistically from the others regarding SST, but all were in accordance with Normative Instruction nº 01, of January 7, 2000, Ministry of Agriculture, regarding the pH and acidity attributes. The fruits of the “Caeteto” and “Moita do Campo” ecotypes showed high levels of total anthocyanins. Altogether, the ecotypes of the grounded environment provided anthocyanins value 14.8% higher than the lowland environment.